The Controversy over Indonesia's Participation in the Board of Peace: A Thematic Analysis of Republika.co.id - Rachmi Kurnia Siregar; S Suwarno; M Mulyati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze how Republika.co.id (March 1-4 edition) organizes and presents the controversy surrounding Indonesia's participation in the Board of Peace based on the Thematic Analysis structure of Braun & Clarke (2012). Methodology: This study uses a constructivist paradigm, a qualitative approach, and Thematic Analysis from Braun and Clarke (2012). The research data consists of ten hard news published in Republika.co.id on March 1-4, 2026, which were purposively selected regarding the controversy surrounding Indonesia's involvement in the Board of Peace. Results: The research identified four main themes: evaluation of Indonesia's policy in the Board of Peace (BoP), the questionable legitimacy of the Board of Peace (BoP), the contradiction between the Board of Peace's peace rhetoric and military practices on the ground, and the delegitimization of the Board of Peace's international leadership. Among the four themes, the evaluation of Indonesia's policy in the Board of Peace (BoP) is the most dominant because it is closely related to the issue of national sovereignty, the consistency of Indonesia's independent and active foreign policy, and Indonesia's diplomatic position amidst increasing geopolitical tensions. The research findings show that Republika.co.id builds a critical and normative narrative by emphasizing moral legitimacy, foreign policy accountability, and humanitarian considerations. Applications/Originality/Value: This research enriches the study of reflexive thematic analysis in journalism studies and provides an understanding of the relationship between editorial orientation, media representation, and the construction of geopolitical reality.